2009
DOI: 10.1097/brs.0b013e3181908ead
|View full text |Cite
|
Sign up to set email alerts
|

Different Ways to Balance the Spine

Abstract: Discrete combinations of muscle activity supported the 3 different sagittal balanced postures in sitting, providing new detail for surgeons, researchers, and therapists to distinguish between different sagittal balanced postures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(55 citation statements)
references
References 49 publications
(33 reference statements)
0
51
2
Order By: Relevance
“…13 Some individuals prefer to sit in a more kyphotic or lordotic lumbar posture compared to pain-free individuals, 13 and these postures are related to differences in the level of muscle activity as measured with electromyographic (EMG) signal. 12 Erector spinae (ES) EMG signal amplitude is reduced when healthy individuals adopt lumbar flexion/kyphosis postures 8,33 and in people with LBP who use this posture naturally. 32 In contrast, ES EMG is increased in extended/lordotic postures in healthy individuals 8,33 and in patients who prefer this posture.…”
Section: T T Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Some individuals prefer to sit in a more kyphotic or lordotic lumbar posture compared to pain-free individuals, 13 and these postures are related to differences in the level of muscle activity as measured with electromyographic (EMG) signal. 12 Erector spinae (ES) EMG signal amplitude is reduced when healthy individuals adopt lumbar flexion/kyphosis postures 8,33 and in people with LBP who use this posture naturally. 32 In contrast, ES EMG is increased in extended/lordotic postures in healthy individuals 8,33 and in patients who prefer this posture.…”
Section: T T Resultsmentioning
confidence: 99%
“…12 Erector spinae (ES) EMG signal amplitude is reduced when healthy individuals adopt lumbar flexion/kyphosis postures 8,33 and in people with LBP who use this posture naturally. 32 In contrast, ES EMG is increased in extended/lordotic postures in healthy individuals 8,33 and in patients who prefer this posture. 3 Earlier studies 3,8,12,32,33 of muscle activation levels in sitting have referred to different patterns of ES EMG signal amplitude in different postures.…”
Section: T T Resultsmentioning
confidence: 99%
“…Although patients with LBP likely to relate to altered coordination between muscles, specifically an inability to activate deep/short lumbar muscles (that extend the lumbar spine) separately from more superficial/multisegmental muscles (that extend larger spine segments, including lumbar and thoracolumbar regions). 2,5 Loss of differential control of these muscles has been identified. 19,29,31 Previous assessments of dissociation of lumbopelvic from thoracic motion have involved dichotomous outcomes as a part of a test battery.…”
Section: Discussionmentioning
confidence: 99%
“…Claus et al (2009) found that increasing anterior pelvic tilt up to the point of achieving a lordosis up to the thoracolumbar junction resulted in the highest measured activity of both TrA and LM compared to slumped and hyperlordotic (extended into the thoracic spine) postures. Therefore, the maintenance of a lumbar lordosis is a cornerstone of specific motor control training (O'Sullivan et al, 2006;Claus et al, 2009;Roussouly et al, 2005).…”
Section: Introductionmentioning
confidence: 90%
“…As the motion capture system used was unable to produce results with reference to a normal spinal posture or vertical reference, the analysis only automatically recruits LM and TrA , and that hyper-and hypo-lordotic postures reduce LM and TrA activity (Claus et al, 2009). This supports the suggestion that FRED exercise could be useful in the restoration of LM and TrA function.…”
Section: Limitations Of the Studymentioning
confidence: 99%